INFLUENCE OF WORK CULTURE, TRAINING, AND COMPENSATION AGAINST THE PERFORMANCE OF EDUCATION OFFICE EMPLOYEES NORTH LABUHANBATU REGENCY - Andi Syahputra Nasution; Syaiful Bahri; Sjahril Effendy Pasaribu (Jurnal Ekonomi, 2022)
This study aims to determine the effect of work culture, training, and compensation on the performance of the Labuhanbatu District Education Office employees. The population of this study was the employees of the Education Office of North Labuhanbatu Regency, totaling 43 employees. The data collection technique in this study is a list of questions (questionnaire), while the data analysis techniques used are classical assumption test, multiple regression, t test, F test, and coefficient of determination. From the t test There is an influence of Work Culture, Training, and Compensation on the Performance of Education Office Employees of North Labuhanbatu Regency. The F test obtained means that Work Culture, Training, and Compensation have a significant effect on performance. The value of the coefficient of determination obtained (R-Square) is 0.494 or 49.40%, indicating about 49.40% of the variable performance can be explained by the variables of Work Culture, Training, and Compensation. The rest is influenced by other variables not examined.